NGHIÊN CỨU ĐỘNG HỌC PHẢN ỨNG CATALAZA ĐƯỢC XÚC TÁC BẰNG PHỨC CỦA Co2+ VỚI AXETYLAXETON (Acac) TRONG HỆ: H2O – Co2+– Acac – H2O2 (1) - Huỳnh, Lê Văn; Xuyến, Nguyễn Văn; Tuyền, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
In this paper, kinetics of H2O2 decomposition reaction (catalaza reaction), catalyzed by complex of Co2+ ion with axetylaxetone (Acac) has been studied. Rate of the reaction depends on different factors such as pH, initial concentration of reactants in the system: H2O - Co2+ - Acac - H2O2. On the base of these studied results the kinetic rule of  the reaction has been established